Guanidinoacetic Acid as a Precursor of Creatine for Cattle - M. Ardalan; E. Batista; C. Armendariz; E. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Creatine serves as an energy-storing molecule in muscle, and in mammals it can be synthesized in the liver from guanidinoacetic acid (GAA). With this study, we evaluated whether GAA supplementation would lead to creatine production in cattle similarly to other species. Because the synthesis of creatine from GAA requires the use of a methyl group, we also evaluated the effect of supplementing methionine, as a methyl group donor, on the synthesis of creatine. Supplemental GAA did increase plasma concentrations of creatine. Also, blood concentrations of arginine, a precursor to GAA, were increased by GAA supplementation, suggesting that arginine use for GAA synthesis was spared by GAA provision. Plasma homocysteine, a marker that is inversely related to methyl group status, was not affected by GAA supplementation when heifers received 12 g/d methionine; however, it was increased by 30 or 40 grams per day of GAA supplementation when methionine was not supplemented. Results suggest that post-ruminal GAA supplementation increases creatine supply to cattle and spares arginine utilization. Moreover, GAA supplementation induced a methyl group deficiency that was resolved with methionine supplementation.
Keywords: creatine; guanidinoacetic acid; homocysteine; methionine